2003
DOI: 10.1590/s0004-27302003000500007
|View full text |Cite
|
Sign up to set email alerts
|

Injeção percutânea de etanol no tratamento de nódulos tiroidianos sólidos, císticos e autônomos

Abstract: RESUMOA injeção percutânea de etanol (IPE) guiada por ultra-som tem sido utilizada para o tratamento de nódulos tiroidianos autônomos, sólidos e cís-ticos. Apresentamos nossa experiência em 50 pacientes tratados, sendo 26 portadores de nódulos sólidos, 17 de nódulos císticos e 7 de nódulos autônomos (NA). Avaliamos os pacientes 1 semana, 1 mês, 3 meses, 6 meses e 1 ano após a IPE. Após 1 ano, os nódulos sólidos reduziram a 74% do volume inicial, os císticos diminuíram 92% sem apresentar recidivas. Um ano após … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
3
0
5
Order By: Relevance
“…Lee and Ahn (11) observed an even greater reduction in volume during longterm followup: 70.1% and 66.1% immediately after PEI and 75.1% and 73.2% after an average of 36 months in sol id and cystic nodules respectively. These authors also showed that PEI was effective in both types of nodules, but even though both types eventually achieved simi lar responses to therapy, the rate of volume reduction and the number of nodules with complete response to treatment were higher among cystic nodules as also shown by others (12,16,17). It is unclear why the ef fects of ethanol are different immediately after PEI and at long term.…”
Section: Discussionmentioning
confidence: 76%
“…Lee and Ahn (11) observed an even greater reduction in volume during longterm followup: 70.1% and 66.1% immediately after PEI and 75.1% and 73.2% after an average of 36 months in sol id and cystic nodules respectively. These authors also showed that PEI was effective in both types of nodules, but even though both types eventually achieved simi lar responses to therapy, the rate of volume reduction and the number of nodules with complete response to treatment were higher among cystic nodules as also shown by others (12,16,17). It is unclear why the ef fects of ethanol are different immediately after PEI and at long term.…”
Section: Discussionmentioning
confidence: 76%
“…Nestas situações, a US é fundamental tanto na orientação da injeção intranodal do etanol (34,35) quanto no posicionamento adequado dos eletrodos para ablação por radiofreqüência (36). Com a detecção precoce de metástases cervicais pela US e pelo prognóstico favorável, é provável que terapias alternativas ganhem mais espaço, especialmente a alcoolização (34,35), poupando os pacientes dos riscos da cirurgia e dos efeitos adversos do radioiodo.…”
Section: Ultra-sonografia Auxiliando O Tratamento De Metástases Cerviunclassified
“…Bianchini and cols. (19) evaluated 50 patients (26 with solid nodules, 17 with cystic nodules, and 7 with autonomous nodules). After 1 year of treatment, solid nodules showed a 74% reduction in the initial volume, whereas cystic nodules decreased by 92% with no recur- rences.…”
Section: Discussionmentioning
confidence: 99%